Psychogenic pain - Marco Lacerenza (Publiediting, 2009)
Complex to be defined, still more difficult to treat, the psychogenic pain stays a challenge for the contemporary medicine from the path-physiologic and therapeutic points of view. Among the several descriptions given to psychogenic pain within the last 30 years, the definition of the DSM IV TR of "pain disorder", better fits the clinical characteristics of this clinical phenomenon. Pain in the last decades has passed by the condition of more common symptom and perhaps a little considered by the scientific point of view, to that of a sophisticated multidimensional experience subtended by precise cerebral areas inclusive in the Pain Matrix. The patient with psychogenic pain conjugates the interest of a more biological and morphological psychiatry with that of a Pain Medicine as multidisciplinary science, where only the meeting of various diagnostic and therapeutic competences can offer the more profit integrated approach.